RESPON PESERTA DIDIK TERHADAP PENERAPAN MODEL PEMBELAJARAN LANGSUNG PADA MATERIUSAHA DAN ENERGI - Lipikuni, Hilary Fridolin; Sunbanu, Sepri Melianto (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The purpose of this study is to describe the results of the application, the completeness of the indicators of student learning outcomes, the completeness of student learning outcomes and the responses of students to learning activities by applying the learning model of subject matter and energy to class VIIIE students in the odd semester of SMP Negeri 6 Kupang academic year 2020 / 2021. This type of research is descriptive research. The subjects in the study were students of class VIIIE SMP Negeri 6 Kupang according to 20 people and teachers (researchers). The data techniques used were observation, tests and questionnaires, while the instruments used in this study were direct learning management sheets, learning outcomes tests and student response form sheets. The research result analysis technique used is quantitative statistical analysis which includes the calculation of the average score, proportion and proportion. Based on the results of quantitative descriptive statistical analysis, the research data in general shows that the application of the direct learning model of subject matter and energy in class VIIIE students in the odd semester of SMP Negeri 6 Kupang in the 2020 / 2021academic year, which allegedly 20 people is optimal.